Energy and exergy evaluation of tri-generation system based on natural gas fired micro-turbine – a case study - Gąsiorowski, Piotr; Mróz, Tomasz (Instal, 2023)
The need of significant reduction of energy supply to building sector joined with new European Union regulations, known as Green Deal, requires application of energy and exergy efficient solutions of energy production and distribution. One of the feasible options is use of co-generation and tri-generation energy systems in the small scale. The article presents the study on application of natural gas fired tri-generation system based on gas fired micro turbine. The system consists of natural gas fired micro-turbine and heat exchanger which produces heat for space heating and ventilation and for cooling energy production in single stage absorption water chiller. The system operates whole year providing fixed electricity production – electrical power NEl , and heating/cooling energy production varying depending on building requirements. As a case study small office building of 1632 m2 useable area has been chosen. Energy and exergy models of evaluated system have been presented. It has been found that annual average energy and exergy efficiencies of the system are low – 0,339 and 0,247 respectively. It is due to the limited utilization of enthalpy and exergy of flue gas in heat exchanger.